Budaya Assuro Maca di Kecamatan Lau, Kabupaten Maros - Risky Rahim; Abdul Rahman A. Sakka (Indonesian Journal of Pedagogical and Social Sciences, 2021)
Abstract. This study aims to find out how the Assuro Maca or Mabbaca Baca tradition is carried out by the Bugis-Makassar tribe located in the Lau area, Maros Regency, South Sulawesi which is often considered by outsiders as idolatrous because of its form of praying for the dead.  has been carried out by the Bugis-Makassar Tribe community which has been carried out for generations as an expression of gratitude for being reunited with the holy month of Ramadan and also aims to pray for the ancestors who have died.  several ways such as at the stage of Observation, Interview, Qualitative data collection, Data Analysis to Data Presentation by Researchers which of course is accompanied by several other journal references related to this research. Keywords: Tradition, Bugis-Makassar, Mabbaca-baca